The Local Government Efforts in Promoting the Development of Tourism Area of Pari Island, DKI Jakarta - Andrey Banyudoyo; Triyanti Anugrahini (Asian Social Work Journal, 2020)
As one of the countries that has rich natural potential, Indonesia is an archipelago country that has extraordinary natural potential. Therefore, to ensure maximum efforts from the implementation of these efforts, a regulation was formed whereby the Central Government authorizes the Regional Government to maximize its potential. the. . The development of national tourism which is quite good in the last five years provides opportunities for each region that has the potential to further develop and maximize all the potential of its region. This then provides an opportunity for the government to build concrete steps in developing an area that originally had potential in the end. can be used to encourage the area to become a tourist area, where these conditions have an impact on the community in the area. The purpose of writing this article is to find out the efforts of the local government in building community welfare through the development of tourist areas on Pari Island. The method used in this writing is a qualitative descriptive type. Data collection techniques in the form of documentation study, observation and in-depth interviews. By taking informants using purposive sampling. The results obtained are that the government has made various efforts to develop the tourism area on Pari Island.